ИССЛЕДОВАНИЕ УСТОЙЧИВОСТИ ЛИНЕЙНЫХ ДИНАМИЧЕСКИХ СИСТЕМ МЕТОДОМ ФУНКЦИЙ ЛЯПУНОВА - Кожаметов, А.Т.; Арзиев, А.Д; Тлеубаева, Г.С. (SCIENCE and SOCIETY, 2019)
The article deals with the question of the stability of linear dynamical systems using the Lyapunov function method. Using positive definite matrices, necessary and sufficient conditions for the existence of a solution to the Lyapunov matrix equation are obtained.
Keywords: Lyapunov function; semidefinite matrix; Lyapunov matrix equation; dynamical systems